2014
DOI: 10.5114/cipp.2014.43101
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to deny group’s wrongdoing and willingness to fight for its members: the role of Poles’ identity fusion with the country and religious group

Abstract: Identity fusion is a powerful visceral feeling of oneness with the group. Dozens of studies have demonstrated that identity fusion is a powerful predictor of endorsement of extreme behavior for the group. However, most research has been conducted with Spanish and/or North-American participants, and focused on the country as the target group. participants and procedureTwo correlational studies were conducted with Polish participants, using measures of identity fusion, group identification, willingness to fight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 16 publications
0
36
0
7
Order By: Relevance
“…The Identity Fusion Scale, which comprises seven items based on a scale by Gómez et al. (; see also Besta, Gómez, & Vázquez, , for previous use in Poland), was adapted to measure overlap between personal and communal identity (α = .93 & .94), with items such as “My city is me” or “I feel immersed in my city.”…”
Section: Methodsmentioning
confidence: 99%
“…The Identity Fusion Scale, which comprises seven items based on a scale by Gómez et al. (; see also Besta, Gómez, & Vázquez, , for previous use in Poland), was adapted to measure overlap between personal and communal identity (α = .93 & .94), with items such as “My city is me” or “I feel immersed in my city.”…”
Section: Methodsmentioning
confidence: 99%
“…This view has the advantage of offering a simple explanation for even quite extreme sacrifice for a group: defending the group is actively conceptualized as defending the self . Supporting this perspective, several studies have found that identity fusion fosters extreme ingroup behavior, including the willingness to fight and die for one's country (Besta, Gómez, & Vázquez, 2014;Swann, Gómez, Huici, Morales, & Hixon, 2010;Swann et al, 2014;Whitehouse et al, 2017), as well as less extreme behavior like ingroup helping (Buhrmester, Fraser, Lanman, Whitehouse, & Swann, 2015;Gómez, Morales, Hart, Vázquez, & Swann, 2011).…”
Section: Partisans' Identity Fusion 3 Partisans' Identity Fusion and mentioning
confidence: 96%
“…This proclivity to recruit and apply kinship-like fusion processes, even at high levels of abstraction with groups that are not defined in terms of any shared biological essence, point to the fundamental importance of fusion-processes in navigating intergroup relations and conflicts. However, in previous demonstrations of extended fusion, participants’ ethnicity was often nested within, overlapped or substantially covaried with the abstract higher-order group in question (e.g., native Spaniards fusing with Spain; Israeli Jews fusing with Judaism; ethnic Poles fusing with the Polish national group or their religion in a country where the vast majority of Catholics are native Poles; [ 16 , 21 , 22 , 32 , 35 ]). Because ethnicity, religion and nationality often co-occur and are conceptually intertwined [ 36 – 38 ], this suggests that some perceptions of shared ancestry or biological essence might already be present in cases of extended fusion with national or religious groups for instance, or at least that the ambiguity of such groups lends itself readily for the extension of kinship-like processes driven by perceptions of shared essence and ancestry.…”
Section: Introductionmentioning
confidence: 99%